The development of Caribbean land resources : the role of surveying and land economy - Symposium on the Development of Caribbean Land Resources the Role of Surveying and Land Economy (1975 : Trinidad); Commonwealth Association of Surveying and Land Economy (London : Commonwealth Assoc. of Surveying and Land Economy, 1976)
09